Trema kaznodziei - Twardy, Jan (Studia Pastoralne, 2026)
The jitters as a fear of public speach is spreading over many people – including the preachers. This article is based mainly on the rhetoric and homiletic publications of German author Albert Damblon. The problem of the jitters isn’t noted in the contemporary Polish homiletics. The author of the article has talked over the term, signs and reasons causing that the jitters occurs – and then has presented different ways to counteract it. The preacher should accept this form of anxiety and use it in a creative way. The main way to counter the effects of jitters is the careful preparation of homily, sermon, conference. Very important is also the spiritual preparation that includes prayer and meditation. The jitters has also its theological dimension. So turning to the hearers with true love and carying about their spiritual welfare the preacher will draw the light and power from Divine Spirit – allowing him to improve the Divine Word ministry and overcome the jitters.